Exploring maritime safety and risk management practices among STIP Jakarta graduates - Marihot Simanjuntak; Larsen Barasa; Marudut Bernadtua Simanjuntak (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This qualitative study addresses the urgent need to enhance safety and risk management practices among graduates of the Maritime Institute Jakarta (STIP Jakarta), including deck officers, engine officers, and shipping professionals. The research objectives are to investigate current safety and risk management practices, examine factors influencing safety culture and risk perception, and assess implications for organisational safety and sustainability. The study employs a qualitative approach, utilising semi-structured interviews and documentary analysis. The sample comprises 70 graduates of STIP Jakarta, with data analysed thematically. Results indicate a strong commitment to safety culture and high compliance with IMO-STCW standards. The study highlights the importance of safety culture, regulatory compliance, and professionalism for ensuring the safety, competence, and sustainability of maritime operations. The findings have significant implications for organisational practice, education, and future research in the maritime industry.